Thermal treatment effect on structural and mechanical properties of Cr–C coatings. (4th March 2018) - Fellah, M.; Aissani, L.; Zairi, A.; Abdul Samad, M.; Nouveau, C.; Touhami, M. Z.; Djebaili, H.; Montagne, A.; Iost, A.
ABSTRACT: In the present study, the effect of thermal treatment on the mechanical and structural properties of chromium carbide coatings with different thicknesses is evaluated. The coatings were deposited by cathodic magnetron sputtering on XC100 steel substrates. Samples were annealed in vacuum, at different temperatures ranging from 700 to 1000°C for 1 h, resulting in the formation of chromium carbides. X-ray diffraction (XRD), microanalysis X/energy-dispersive X-ray spectrometer (EDS), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy analysis were used to characterise the samples. Mechanical properties were evaluated by nano-indentation tests and the residual stress was calculated with the Stoney formula. The XRD analysis suggests the formation of the Cr7 C3, Cr23 C6 carbides at 900°C. For thin films, they transformed totally to ternary (Cr, Fe)7 C3 carbides and their partial transformation has been observed in the case of thick films at 1000°C, without the formation of Cr3 C2 . The EDS and XPS showed the diffusion mechanism between the chromium film and the steel substrate for the Cr, Fe, C, O elements during the annealing treatment. The increase of chromium film thickness from 0.5 to 2.64 µm, contributed to the significant enhancement of mechanical properties such as hardness (H) (from 12 to 26.3 GPa) and Young's Modulus (E) (from 250 to 330 GPa), respectively.